Urgensi Pemertahanan Bahasa Ibu di Sekolah Dasar - Hamidulloh Ibda (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
Mother tongue defense is an effort to preserve the language treasures in Nusantara. Mother tongue as part of Indonesian wealth must be kept early, especially in elementary school level. If elementary school children lose their native language, it will deprive their own culture and character. Damage to language in children is a clear proof that maintaining the mother tongue is very important. Mother tongue defense in addition to strengthening in language learning can also be done through cultural diversity, maintaining ethnic identity, social adaptability, enhancing children’s sense of security and enhancing linguistic sensitivity. In addition, it needs family support, language environment in schools, language celebrations and mass media support as forming the public language.